Pengembangan Modul Ajar Berbasis Kearifan Lokal Pada Materi Fungsi Komposisi - Rahmawati, Erna; Prabawati, Mega Nur (Polinomial : Jurnal Pendidikan Matematika, 2026)
This study aims to develop an ethnomathematics-based teaching module for the topic of composite functions. The research employed the ADDIE design model, limited to four stages: Analysis, Design, Development, and Implementation. Data were collected through questionnaires completed by four certified teachers who served as expert validators, as well as through student response questionnaires used to assess the practicality of the module. The questionnaire data were analyzed quantitatively and interpreted using predetermined assessment criteria to determine the quality of the product. The validation results indicated that the module achieved an average score of 81.25%, demonstrating a high level of validity. Moreover, the practicality test yielded an average score of 89.3% from students, indicating that the module is highly practical for classroom use. Based on expert evaluations and student responses, the ethnomathematics-based teaching module on composite functions meets the criteria of being both valid and practical.